Changes in water levels of Prosna (Bogusław profile) in the years 1973-2017 - Ptak, Mariusz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The thesis presents long-term changes in water levels of Prosna, one of the main rivers in Wielkopolska, i.e. a region that commonly is considered as one of the least water-rich in Poland.It was found that in the last 40 years, average annual water levels of Prosna were characterized by a downward trend of 7.8 cm?dec-1 and werestatistically significant at p=0.05 and also p=0.01.In all months, the water level dropped, although statistically it was significant in seven cases.The largest reduction in monthly average water levels (statistically significant, p = 0.05) was in August and December and it was progressing at a rate of 13.2 and 12.3 cm?dec-1.The consequence of this ongoing trend may be, among others, deterioration of living conditions of ichthyofauna, or worse water quality of Prosna.
Keywords: water levels; river; climate changes; Prosna